2020
DOI: 10.1051/meca/2020016
|View full text |Cite
|
Sign up to set email alerts
|

Thermal potential of a geothermal earth-to-air heat exchanger in six climatic conditions of México

Abstract: In this paper, the thermal and ventilation potential of a geothermal Earth-to-Air Heat exchanger (EAHE) is studied for six weather in Mexico. The cities for the study and their climate were Villahermosa (hot-humid), Merida (hot-sub humid), Monterrey (dry), Juarez City (very dry), Zacualtipan-Hidalgo (warm-humid) and Mexico City (warm-sub-humid). The thermal behavior of the EAHE was modeled numerically for the corresponding warmest and coldest days of the year for each city and three values of Reynolds number. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…It has been found that the thermal conductivity of soil decreases as the salinity of soil increases due to groundwater entering the soil through capillary (Rodríguez-Vázquez, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been found that the thermal conductivity of soil decreases as the salinity of soil increases due to groundwater entering the soil through capillary (Rodríguez-Vázquez, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors found several relations among the geometric displacements of the ducts and the EAHE performance. As for the humidity, the reduction of its levels increases significantly the ventilation potential for EAHE, from the results in different cities of México given in (RODRÍGUEZ-VÁZQUEZ et al, 2020). Moreover, it is also worth to mention that EAHE can be coupled with other technologies, forming hybrid systems, such as the photovoltaic/thermal ones presented in (LI et al, 2019), just to cite a recent example.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been done on coupled systems where the EAHE is coupled with other devices 15–20 to improve its efficiency or utility. Some researchers have studied the effect of the soil composition 21–25 and climatic conditions 26–31, particularly an arid climate 30, 31, on the performance of EAHE. The studies highlight the potential of EAHE systems in providing thermal comfort in arid regions 30, 31.…”
Section: Introductionmentioning
confidence: 99%